Creating Evidence of Social Impact Through Skilling of First-Graduate Girls of the Family - Anindya, Devi (Digital Repository of Theses, 2026)
This study examines the influence of a structured Life Skills and Mentorship intervention on the educational engagement, psychosocial development, decision-making capacities, and career aspirations of adolescent girls and young women in low-opportunity contexts. Despite progress in access to education, many girls continue to face entrenched barriers including restrictive gender norms, limited exposure to professional pathways, financial hardship, and constrained decision-making environments. The research aimed to understand whether targeted life-skills training combined with sustained mentorship can strengthen agency, enhance future readiness, and support progression toward higher education and meaningful careers. Using a mixed-methods design, the study drew on survey data, reflective responses, and qualitative insights from participants in government and government-aided colleges. Quantitative analysis compared mentored and non-mentored groups across indicators such as confidence, leadership intention, educational motivation, decision-making, problem-solving, and aspirational clarity. Qualitative narratives provided depth into students’ experiences of internal change, relational support, and exposure to new opportunities. The analysis was guided by behavioural, psychosocial, and capability-expansion frameworks that emphasise the role of self-efficacy, reflective capacity, and enabling environments in adolescent development. Findings revealed consistent positive outcomes associated with mentorship participation. Mentored girls reported enhanced confidence, reduced self-doubt, and a stronger sense of leadership identity. They demonstrated greater intrinsic motivation for learning, clearer articulation of long-term goals, and increased ability to evaluate options and consequences when making decisions. The intervention also broadened career aspirations, with many participants expressing interest in high-growth professional fields previously perceived as inaccessible. Improvements in communication, emotional resilience, peer relationships, and civic awareness further reflected the holistic developmental impact of the programme. The study concludes that mentorship, when combined with structured life-skills training, serves as a powerful developmental mechanism capable of expanding girls’ capabilities, aspirations, and sense of agency. These findings highlight the need to integrate mentorship models and socio-emotional learning into mainstream higher-education systems, particularly within resource-constrained settings. Strengthening such interventions can enhance educational continuity, support transitions into skilled employment, and contribute to broader gender-equity and economic development goals.